Vocabulary Improvement for Language Learner: A Challenge and Perceptions: A Challenge and Perceptions - Yuliana, Yuliana; Agustin, Ariya; Agustinasari, Evi; Purwanto, Muhammad Bambang (PT FORMOSA CENDEKIA GLOBAL, 2024)
English language education at the college student level is an important aspect of global higher education today. However, college students face various challenges that affect the effectiveness of English language learning. This research aims to find out the various challenges experienced by students to master English in an academic environment. Ten students enrolled in the D3 Hospitality study program for the third semester were interviewed for this study, which was carried out utilizing qualitative methodologies. The results revealed a number of challenges experienced by students in learning English such as difficulty understanding the material, complicated grammar pronounced and difficult to remember, lack of vocabulary mastered, differences between writing and pronunciation of English and feeling less confident when speaking English. The study also identified several strategies that can help address these challenges in hopes of improving English learning outcomes at the Polytechnics.